Sampling with a Rope - a Worked Example - Satyamurthi, K. R. (Indian Forester, 1979)
The author in a previous paper "Sampling with a rope - a novel and useful method" published in January, 1979, Indian Forester Vol.105, No.1 has described a new method of conducting surveys for estimating basal area of a stand of trees. Here the practical verification of the above said theory is done. For this purpose both a real forest stand at Lachhiwala Range, East Dehra Dun Division, Compartment Number 2 and a theoretical basal area of the shapes given in Figure 4 (Text) were considered. This study proves the validity of the Sampling with a Rope Theory.